Incremental value of feature-tracking cardiac magnetic resonance imaging in detecting myocardial dysfunction in patients with idiopathic ventricular arrhythmias. (8th February 2021) - Nikolaidou, C; Kotanidis, C; Leal-Pelado, J; Kouskouras, K; Vassilikos, VP; Karvounis, H; Karamitsos, TD
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cardiac magnetic resonance (CMR) imaging can identify the underlying substrate in patients with ventricular arrhythmias (VAs) and normal echocardiography. Myocardial strain has emerged as a superior index of systolic performance compared to ejection fraction (EF), with an incremental prognostic value in many cardiac diseases. Purpose: To assess myocardial deformation using 2-D feature-tracking CMR strain imaging (CMR-FT) in patients with frequent VAs (≥500 ventricular premature contractions (VPC)/24 hours; and/or non-sustained ventricular tachycardia), and structurally normal hearts on echocardiography without evidence of coronary artery disease. Methods: Sixty-eight consecutive patients (mean age 46 ± 16 years; 54% female) and 72 healthy controls matched for age and body surface area were included in the study. CMR imaging was performed on a 1.5T Magnetom Avanto (Siemens, Erlangen, Germany) scanner using a standard cardiac protocol. Results: CMR showed normal findings in 30 patients (44%), while 16 (24%) had previous myocarditis, 6 (9%) had a diagnosis of non-ischaemic cardiomyopathy (NICM), 15 (22%) were diagnosed with VPC-related cardiomyopathy, and 1 patient had subendocardial infarction [excluded from strain analysis]. Mean left ventricular EF (LVEF) in patients was 62% ± 6% and right ventricular EF 64% ± 6% (vs. 65% ± 3% and 66% ± 4% in controls, respectively). Compared to control subjects, patients with VAs had impaired peak LV global radial strain (GRS) (28.88% [IQR: 25.87% to 33.97%] vs. 36.65% [IQR:33.19% to 40.2%], p < 0.001) and global circumferential strain (GCS) (-17.73% [IQR: -19.8% to -16.33%] vs. -20.66% [IQR: -21.72% to -19.6%], p < 0.001, Panel A). Peak LV GRS could differentiate patients with previous myocarditis from patients with NICM and those with VPC-related cardiomyopathy (Panel B). Peak LV GCS could differentiate patients with previous myocarditis from patients with NICM (Panel C). Peak LV GRS showed excellent diagnostic accuracy in detecting patients from control subjects (Panel D). In a multivariable regression model, subjects with a low GRS (<29.91%-determined by the Youden's index) had 5-fold higher odds of having VAs (OR:4.99 [95%CI: 1.2-21.95]), after adjusting for LVEF, LV end-diastolic volume index, age, sex, BMI, smoking, hypertension, and dyslipidaemia. Peak LV global longitudinal strain (GLS) and RV strain indices were not statistically different between patients and controls. Conclusion: Peak LV GRS and GCS are impaired in patients with frequent idiopathic VAs and can detect myocardial contractile dysfunction in patients with different underlying substrates. Our findings suggest that LV strain indices on CMR-FT constitute independent markers of myocardial dysfunction on top and independently of EF.